Resistencia a antimicrobianos en bacterias aisladas en la cadena de producción avícola - López, V. (2021)
Bacterial resistance to antimicrobials is a global problem. A possible cause of the emergence of resistance\nis their use as growth promoters. This can cause therapeutic failures and increase the transmission of\nresistant bacteria. The objective of this work was to determine the sensitivity to antimicrobials of isolated\nbacteria from poultry and products for human consumption. Sixty samples were studied and Escherichia\ncoli, Salmonella spp. and Enterococcus faecalis were isolated. Around 80 % of the farm samples showed\ncounts of >103 UFC/g for E. coli and 95 % for E. faecalis; 70 % of the refrigerated samples showed counts\nof >103 UFC/g for E. coli, and 85 % of the market samples showed counts of > 103 CFU /g for E. faecalis, 15 % for E. coli; and 5 % developed Salmonella spp. Of the 53 E. coli isolations, 47.1 % were resistant to fluoroquinolones, 9.4 % to third-generation cephalosporins, and 3.8 % to colistin. Of the 39 E. faecalis isolated strains, one was resistant to ciprofloxacin, and none to vancomycin. The isolated Salmonella spp. was resistant to ciprofloxacin. Our results reveal the need to intensify sanitary and hygiene controls poultry manipulation chain and implement improvements to pathogens reduction.